Technology and the environment in general equilibrium - Rasmus Kehlet Berg (University of Copenhagen, Department of Economics, 2022)
The PhD dissertation consists of three self-contained parts that deal with representing technology in environmental economic models. All three parts offer ways for improving economic models by leveraging knowledge on technologies collected by other academic disciplines. The first two parts explore new ways for economic models to capture the potential for renewable energy technologies. One of the main challenges of reaching net-zero greenhouse gas emissions is that most cheap, renewable energy generation is intermittent; the availability of wind or solar power depends on natural conditions, such as wind speed and cloud cover. We develop a technology-rich model for electricity and district heat systems and show that it captures the key effects of intermittency. We show that the model can be solved efficiently alongside conventional economic models using smoothing techniques. This integrated framework can be used to evaluate policies e.g. aimed at lowering emissions through electrification of polluting economic activity, such as transportation, using intermittent renewable energy. The problem of intermittency can be solved using a combination of four technologies: Back-up capacity of more flexible dispatchable electricity producing plants, expansion of the transmission grid to enable more trade in electricity, flexible demand technologies, and electricity storage. The second part of the dissertation uses the technology-rich model from part one to investigate the value and potential of electricity storage. We show that in the Danish context, investing in electricity storage reduces greenhouse gas emissions and lowers average prices significantly. However, the investment costs of lithium-ion batteries prohibit them from being cost-effective until after 2030. We show that this is largely a result of neighboring countries' strategy for investments in storage technologies and intermittent renewables, thus emphasizing the importance of a technology-rich model that includes details on the transmission grid. Finally, while parts one and two focus on the scope for emission reductions through renewable energy, part three focuses on modeling reductions through abatement technologies. We provide a novel framework that allows us to use much more detailed data on abatement technologies than state of the art environmental economic models. We show under what conditions current best practices over- and underestimates abatement costs when technology data is not appropriately represented in the economic model.
Keywords: 330